Geographic Variations and Trends in Primary and Revision Knee and Total Hip Arthroplasties in the United States - Hilibrand, Ari S. (JB JS Open Access, 2020)
BACKGROUND: Over 1 million joint arthroplasties are performed annually in the United States. Ideally, as devices and surgical techniques improve, the number of revision arthroplasties relative to primary arthroplasties should decrease. To our knowledge, this is the first study to evaluate state-by-state disparities in the ratio of revision to primary knee arthroplasty (unicompartmental and total) and total hip arthroplasty (THA). METHODS: The National Inpatient Sample was used to identify patients who had undergone primary or revision knee arthroplasty or primary or revision THA from 2001 to 2011. Demographic characteristics, surgical rates, and revision ratios (the number of revision procedures divided by the number of primary procedures) were determined for the United States as a whole and by state. RESULTS: During the study window, 47 states were sampled. For knee arthroplasty, 1,251,484 patients were identified: 91% underwent primary procedures and 9% underwent revision procedures. Compared with the primary knee arthroplasty cohort, the revision knee arthroplasty cohort had a younger mean age, had more male patients, and had more chronic conditions and longer hospitalizations (p < 0.001 for each). Over the years studied, the mean age of patients who had undergone primary knee arthroplasty decreased 1.8 years (p < 0.0001) and the mean age of those who had undergone revision knee arthroplasties decreased 2.4 years (p < 0.0001). The national revision ratio remained unchanged at around 0.1 (p = 0.8792). However, there was a 2.2-fold variation in revision ratio by state (revision ratio state range, 0.065 to 0.141). For THA, 614,638 patients were identified: 85% underwent primary procedures and 15% underwent revision procedures. Compared with the primary THA cohort, the revision THA cohort had an older mean age, had fewer male patients, and had more chronic conditions and longer hospitalizations (p < 0.001 for each). Over the years studied, the mean age of patients who had undergone primary THA decreased 1.5 years (p = 0.0016), whereas patients who had undergone revision had no significant age trend (p = 1.0000). Unlike for knee arthroplasty, the national THA revision ratio trended downward (0.24 evolved to 0.18, p = 0.0016), and there was a 2.1-fold variation in the revision ratio by state (revision ratio state range, 0.119 to 0.248). CONCLUSIONS: This study found significant variability in state-by-state revision ratios. It also found that the national revision ratio stayed relatively steady for knee arthroplasty but was decreasing for THA, and that patients who had undergone revision knee arthroplasty were getting younger, whereas patients who had undergone revision THA were not. These discrepancies suggest divergent histories for primary knee arthroplasty and THA and warrant further detailed evaluation. LEVEL OF EVIDENCE: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.